The evolving role of response-adapted PET imaging in Hodgkin lymphoma. (April 2016) - Coyle, Michael; Kostakoglu, Lale; Evens, Andrew M.
18 F-fluorodeoxyglucose positron emission tomography with (FDG-PET) has a well-established role in the pre- and post-treatment staging of Hodgkin lymphoma (HL), however its use as a predictive therapeutic tool via responded-adapted therapy continues to evolve. There have been a multitude of retrospective and noncontrolled clinical studies showing that early (or interim) FDG-PET is highly prognostic in HL, particularly in the advanced-stage setting. Response-adapted treatment approaches in HL are attempting to diminish toxicity for low-risk patients by minimizing therapy, and conversely, intensify treatment for high-risk patients. Results from phase III noninferiority studies in early-stage HL with negative interim FDG-PET that randomized patients to chemotherapy alone versus combined modality therapy showed a continued small improvement in progression-free survival for patients who did not receive radiation. Preliminary reports of data escalating therapy for positive interim FDG-PET in early-stage HL and for de-escalation of therapy [i.e. bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine and prednisone (BEACOPP)] for negative interim FDG-PET in advanced stage HL (i.e. deletion of bleomycin) have demonstrated improved outcomes. Maturation of these studies and continued follow up of all response-adapted studies are needed. Altogether, the treatment of HL remains an individualized clinical management choice for physicians and patients. Continued refinement and optimization of FDG-PET is needed, including within the context of targeted therapeutic agents. In addition, a number of new and novel techniques of functional imaging, including metabolic tumor volume and tumor proliferation, are being explored in order to enhance staging, characterization, prognostication and ultimately patient outcome.